PERANAN SUSTAINABLE HRM PRACTICE TERHADAP JOB SATISFACTION DAN TURNOVER INTENTIONS PADA PERUSAHAAN MANUFAKTUR DI KOTA BATAM - Farid, Ridhayati; Juriana, Elvi; Asri, Dhita Hafizha (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the impact of sustainable HRM practices on job satisfaction and turnover intentions, using work as a mediator. Sustainable HRM practice is an independent variable, while the dependent variable consists of job satisfaction and turnover intentions. This study uses the mediating variable, namely the meaning of work. The research was conducted by covering the population of employees of manufacturing companies in Batam City and collecting data using Google Form questionnaires. There were 330 respondents used as samples in this study, using PLS-SEM with Smart PLS 3 and SPSS software. The results of this study prove that sustainable HRM practice affects job satisfaction and turnover intentions. Meaning of work can affect job satisfaction. The results of this study also prove that sustainable HRM practice can affect job satisfaction with the meaning of work as a mediating variable. Keywords: Sustainable HRM Practices; Job Satisfaction; Turnover Intentions; Meaning of Work